7 - TREINAMENTO CONCORRENTE E CONSUMO DE REFRIGERANTE: EFEITO NA MUSCULATURA DE RATOS. CONCURRENT TRAINING AND SOFT DRINK CONSUMPTION: EFFECT ON THE MUSCULATURE OF RATS. (Fiep Bulletin - online, 2021)
In recent decades, due to modernity, food patterns have undergone changes, increasing the consumption of sugary and industrialized drinks such as soft drinks that contribute to weight gain and the appearance of morbidities. In this context, physical training emerges as a way to fight excess weight and increase physical capacities. Thus, the objective of the study was to verify the effect of concurrent training on skeletal striated muscles of animals submitted to soda consumption. Twenty-two male Wistar rats were used as samples, distributed in four groups (n= 32): Control (C [n= 8]); Refrigerant Control (CR [n= 8]); Concurrent Training (T [n= 8]); Concurrent Training with Refrigerant (TR [n= 8). The aerobic training protocol was composed of 3 weekly sessions at 80% of the anaerobic threshold and the strength training was composed of 4 series of 10 aquatic jumps. After preparation and measurement of muscle tissue, the values ??for the smallest diameter of the muscle fibers were obtained. When comparing the averages of the diameter of the sample groups, the CR and T groups showed significant results in relation to the C group (p<0.05). There was muscle hypertrophy in the TC group in relation to the TCR group (TC: 39.99 µm vs TCR: 39.22 µm), however, with no statistically significant difference (p> 0.05). Thus, the study concludes that CT was efficient for hypertrophy in muscle mass, being superior in the group where there was no soft drink intake. However, the change was not statistically significant, however, both the intake of soda and the practice of concurrent training resulted in a significant increase in the diameter of muscle fibers, compared to the control group.